Secretory PLA2 specific single domain antibody neutralizes Russell viper venom induced cellular and organismal toxicity - Kaur, M.; Dubey, A.; Khatri, M.; Sehrawat, S. (Elsevier, 2019)
Despite continued destruction of human lives by snakebites, appreciable improvements in immunotherapies have not been made. We selected and characterized venom-specific single domain antibodies (sdAbs) from a constructed phage display library of camelid variable region of heavy chain of the heavy chain antibodies (VHHs). Secretory phospholipase A2-specific sdAbs neutralized venom-induced toxicity in vitro and in vivo. Such monoclonal sdAbs could serve as an alternative to help manage snakebites to save lives.
Keywords: Phage display; Monoclonal Ab; sdAb; RVV envenoming